Optimalisasi dalam Seleksi Bibit Kelapa Sawit Unggul Menggunakan Metode TOPSIS - Ahmad Rafi Rusydi (SEULANGA SYSTEM PUBLISHER, 2023)
The quality of palm oil that will be produced from oil palm has a great influence on the type of oil palm seeds planted. The process from the maintenance of oil palm, to the process of processing palm oil into palm oil. The purpose of this research is to build a decision support system that can assist in the selection of superior oil palm seeds based on the website. The method used is Technique for Others Preference by Similarity to Ideal Solution (TOPSIS) which is a multi-criteria decision-making method. The principle of this method is that the chosen alternative must have the closest distance to the positive ideal solution and the farthest distance to the negative ideal solution. In this method, you can choose or make decisions by determining the weighting value for each attribute and then proceed with a ranking process that will provide the best alternative from one with the alternative with the highest priority value. This method provides an ideal solution for farmers in making decisions about which superior oil palm seeds to plant. The processed data is divided into 3 varieties, namely Dura, Pisifera, and Tenera. Each variety has different characteristics. The results of the research can be ranked correctly as a reference in determining decision making in the selection of the best seeds. This research can be used as a recommendation in the calculation for the selection of superior oil palm seeds.